THE EFFECTIVE EVALUATION OF DIGITAL REPRODUCTIVE HEALTH LITERACY INTERVENTION ON SERVICE COMPETENCIES OF HEALTH PROVIDERS IN ADOLESCENT AND YOUTH HEALTH CLINICS IN THAILAND - Intarakamhang, Ungsinun; Dheva-aksorn, Kirana; Prasittichok, Pitchada (Ethiopian Journal of Reproductive Health, 2023)
INTRODUCTION: The global reproductive health remains concerning due to the insufficient knowledge and understanding among healthcare providers. This knowledge gap also extends to their limited ability to utilize technology for delivering services. The purpose of this research was to find an intervention for Digital Reproductive Health Literacy (DRHL) to enhance service competencies. METHODS: The randomized controlled trials (RCTs) were conducted January to July 2023. The 60 participants aged 20 to 60 working in adolescent and youth clinics were selected through random assignment and 30 allocated to 12 hours intervention in 6 modules, consisted of knowledge, digital skills, communication skills, provider attitudes, digital-based services, and networking skills. 30 participants were assigned in the control group. The data were collected using DRHL scale with reliability of 0.97, and Discriminant power of 0.2 to 0.8. Data were analyzed using MANCOVA. RESULTS: The results showed that health providers in the experimental group had significantly a higher mean score of DRHL (Mean = 90.83, 80.60) and competencies (Mean 69.60, 62.00) than control group at after treatment and follow up (Mean = 93.13, 81.13; Mean= 70.57, 62.97, p<.01). Specially, in the experimental group indicted that mean score of the DRHL and competencies by domains at follow-up were higher than the mean score at before treatment (p < .05). CONCLUSION: Human resources specialists or administrators could apply DRHL intervention to promote DRHL and competencies for health providers working in adolescent and youth health clinics.